Pengaruh Modifikasi Pisau Pemotong Dan Kecepatan Putaran Terhadap Unjuk Kerja Mesin Pemipih Dan Pemotong Adonan Mie - Qosim, Nanang; Qiram, Ikhwanul; Rubiono, Gatut (Virtual of Mechanical Engineering Article, 2018)
In this study modifications to the cutting knife and rotational speed were carried out. With blade variations of 2mm, 3mm and 4mm and rotational speeds of 300, 900 and 1500 rpm. After the research process is carried out, the noodle product tests include the length of the noodles, thickness, and elongation values. For testing, the length and thickness of the noodles used a measuring device ruler and calipers and testing the value of elongation was done by tensile tests. The results of the study showed the percentage shrinkage of 0.0% noodle dough weight. This shows the test equipment is working optimally. The faster the rotation of the motor the difference between long and thick noodles tends to increase. This shows that the rotation speed has an influence on the performance of the flattening machine and noodle dough cutter. The faster the motor rotation, the elongation value of noodles tends to decrease. This is due to the rotation speed of the motor that affects the occurrence of broken noodles. The greater the size of the noodles the risk of breaking up the noodles decreases. The faster the motor rotation, the greater the capacity produced.